Magic Bookmark: A Nonintrusive Electronic System for Functionalizing Physical Books. (11th October 2021) - Bairaktaris, Georgios; Siderov, Hristo; Celebiler, Deniz; Kolii, Corinne; Frohlich, David M.; Sporea, Radu A.
Abstract : The use of physical paper is often preferred due to its unique physical properties that improve various aspects of reading. However, digital media and information are more engaging, diverse, and up to date, thereby challenging the existence of paper in our everyday life. By combining the two types of media in a seamless way, the interactivity of multimedia content can complement the reading experience, maintaining the unique feel of paper books. The current state of the art addressing this application negatively impacts the reading experience and often does not consider the manufacturability and sustainability of the proposed solutions. Herein, the Magic Bookmark, a technical solution for automatically recognizing the open page of a physical book, to provide seamless augmentation without changing the user's behavior and experience significantly is introduced. Three alternative solutions are implemented, with various degrees of ease of use, manufacturability at scale, and reliability of data reading. The optimal realization is found to be a reflective optical readout array, for which routes to implementation that may allow blending the graphical and functional aspects of the augmented book are proposed. Abstract : Adding value to paper without affecting its unique physical properties is proposed, by associating digital multimedia content to printed information. The Magic Bookmark is a technical solution for automatically recognizing the open page of a book. Printed hybrid electronics allow for the seamless integration of the required functionality within a book, without an impact on the reader's behavior.